LIÊN KẾT HIĐRO CHUYỂN DỜI XANH VÀ TƯƠNG TÁC AXIT–BAZƠ TRONG CÁC PHỨC GIỮA ĐIMETYL ETE VÀ DẪN XUẤT THẾ HALOGEN CỦA NÓ VỚI CO2 - Hiền, Đỗ Thanh; Thu Trang, Nguyễn Thị; Huế, Trần Thành; Hoà, Hoàng Văn; Trung, Nguyễn Tiến (Vietnam Journal of Chemistry, 2012)
The calculations at the MP2/aug-cc-pVDZ high level of theory were performed to study on Lewis acid-base interaction and hydrogen bond in the complexes obtained by the interactions of  dimethyl ether and its halogen–substituted derivatives with CO2. Lewis acid-base interactions were observed for the complexes G1, G1.2, G1.3 and G1.4, however the blue shifting hydrogen bond was found only in G1.4. The specific classfication of hydrogen bond in G1.3 needs to be verified on the basis of experimental methods. The obtained results show that the replacement of two H atoms of CH3 group in dimethyl ether by two halogen ones leads to the increase in strength of complexes in the order of flouride-substituded derivative to chlorine one and to bromide one. The magnitude of hydrogen bonding interaction is also increased remarkably upon this substitution. As the result, G1.4 is the most stable complex in the investigated ones with calculated binding energy about 12.3 kJ.mol-1 including both ZPE and BSSE corrections.